1996
DOI: 10.1103/physrevlett.77.3522
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Be Atoms inC60Fullerene Cages:Be@C60

Abstract: Radioactive endohedral 7 Be@C 60 can be detected using radiochemical and radiochromatographic techniques in the final solvent. Such a 7 Be atom can penetrate into the C 60 cage to produce 7 Be@C 60 by a recoil process of the nuclear reactions. An ab initio molecular dynamics simulation was carried out to demonstrate that a direct insertion process is really possible. Both the experimental and the theoretical results were consistent with each other. [S0031-9007(96)01431-7]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 11 publications
1
109
1
1
Order By: Relevance
“…(It should be noted that we have also measured the half-life of 7 Be in a sample of 7 Be@C60. The results have been presented in another paper 15,16) ). Finally, we obtained the half-life (T 1=2 ) for the sample of Be metal crystal ( 7 Be), which is 53:25 AE 0:04 days.…”
Section: Resultsmentioning
confidence: 83%
“…(It should be noted that we have also measured the half-life of 7 Be in a sample of 7 Be@C60. The results have been presented in another paper 15,16) ). Finally, we obtained the half-life (T 1=2 ) for the sample of Be metal crystal ( 7 Be), which is 53:25 AE 0:04 days.…”
Section: Resultsmentioning
confidence: 83%
“…The residual activities in the solution from 41 Ar, 133g Xe, 135g Xe, or 85m Kr were attributed to the existence of *NG@C 60 compounds. HPLC could be adopted for the separation of the formed endohedral radiofullerenes of 7 Be@C 60 , 85m Kr@C 60 , and 135 Xe@C 60 [37,38] . A recent work [39] studied the n,γ-reaction of metallofullerenes of Tb, Sm and Sc 3 N@C 80 and found that possibly unfavorable geometry of target/projectile system can not explain low yield observed so far.…”
Section: Radiolabeling Of Carbon Nanomaterialsmentioning
confidence: 99%
“…Ab initio calculations on the stability of MC 60 (M = Sc, Y and K) and Si atom-doped endohedral C 60 have been reported in the literature (Misra et al 2012: Suzuki et al 1994Ibrahimand El-Haes 2005;Lu et al 2001). Furthermore, doping of radioactive elements, such as beryllium (Be) (Ohtsuki et al 1996) and gadolinium (Gd) (Kubozono et al 1996), has been found to be properly encaged inside a C 60 cluster, leading to substantial applications in nuclear wasting disposal such as nano-container radio activities. Indeed, the discovery of fullerenes has opened the gate for the production and investigation of much more suitable material building blocks, which could be used as drug deliverers in medical applications and/or possible superconductors in technological applications (Alzahrani2012).…”
Section: Introductionmentioning
confidence: 99%